IMPROVEMENT OF BUSINESS CAPACITY AND MANAGEMENT IN THE SERIKAT SAUDAGAR NUSANTARA UMKM COMMUNITY BANDAR LAMPUNG - Mawardi Mawardi; Abizar Abizar (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Micro, Small and Medium Enterprises (UMKM) is a business sector that has proven to be very important in overcoming the consequences and impacts of the economic crisis that has hit Indonesia. The micro, small and medium enterprises sector has been able to contribute in boosting Indonesia's economic growth so far. The strategic position of UMKM community players because this sector has several advantages over large businesses. The advantages of this sector include the ability to absorb labor and use local resources, and its relatively flexible and populist business. The Serikat Saudagar Nusantara UMKM Community is a UMKM community with 104 members, this community aims to give birth to powerful Lampung UMKM. based on observations and interviews of the management and members of the UKM, the Serikat Saudagar Nusantara UMKM Community, they are still lacking in terms of management, marketing and financial reports so that they really need assistance and improve skills in the form of management, marketing, and financial reports. The method of service and activities carried out is to explore problems, found urgent problems, namely management, marketing and finance so that training and assistance in management and marketing technology aspects are needed. The results of this activity have been the implementation of the management function (POAC) in the activity plan, improving marketing skills and good management so that there is an increase in turnover at UMKM community